(untitled) (GEON Journal (Management, Organizations and Business), 2019)
The phenomenon of informality has been highlighted as one of the factors that affect the labor market in Colombia and the world, not only because of its effect on the economy, but also because of its accelerated growth. The present work is directed to identify the main reasons of permanence of the informal merchants in the streets of the San Isidro neighborhood, where the municipal market square functioned, in the city of Villavicencio, Colombia. The previous thing, has been product of a decade of failures on the part of the institutionality without still the decision on the ordering of this zone is known; generating an inadequate management and disposal of organic waste as well as the invasion of public space. Additionally, it has been shown that temporary solutions such as the eviction of jobs only bring violence in the places where it is carried out. Therefore, the permanence is given in terms of: income level, flexible hours, autonomy, experience and knowledge of the market; adding that formalization is not considered as a viable alternative to trade.